Public Service Delivery in a Conflict and Natural Disaster Region - Rahmayanti, Krisna Puji (UI Scholars Hub, 2018)
Public service quality is the reflection of the government performance, particularly in the disaster and conflict-affected regions. In the post-conflict area, the government has difficulty to increase government performance because conflict affect public service delivery. Moreover, the disaster-affected region needs a quick response to stabilize public service delivery. Aceh is one of conflict and natural disaster affected area in Indonesia which suffered in all aspect include in the public service delivery. In these circumstances, a reconstruction process to revitalize service delivery is an important aspect. Therefore, this review paper aims to analyze public service delivery during conflict and tsunami hit Aceh. The result found that the lack of public service capability triggered the conflict. During conflict period, the resentment toward government manifested in the destruction of the public buildings. Conflict period in Aceh made many public buildings were destroyed or inactive which eventually impede public service. The phenomenon of the tsunami, in one hand, ended the conflict, but on the other hand, increased the damage of the public service system in Aceh. Therefore, the reconstruction process in Aceh which comes from state and national or international non-state play crucial role to build public service delivery.